2006
DOI: 10.1002/ijc.21741
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological characteristics of colorectal cancers with loss of imprinting of insulin‐like growth factor 2

Abstract: Loss of imprinting (LOI), the biallelic expression of an imprinting gene, of insulin-like growth factor 2 (IGF2) has been reported to be associated with colorectal carcinogenesis because of its high prevalence in normal colorectal mucosa as well as cancerous tissue in patients with colorectal cancer. However, the characteristics of colorectal cancer associated with IGF2 LOI have not been clearly demonstrated. In this study, we investigated the IGF2 LOI status of tumor and normal mucosa in 255 consecutive patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…Our results showed that CRCs with IGF2 LOI mainly occur in the proximal colon; statistically significant relationships were observed between a proximal tumor site and IGF2 LOI in univariate analysis and logistic regression analysis adjusting for age and sex. This finding agrees with the finding of a previous report that CRC with IGF2 LOI is preferentially located in the proximal colon [21]. In the present study, IGF2 LOI seemed to be another factor of carcinogenesis on the right side of the colon independent of aging, whereas our colleagues have reported that right-side colorectal neoplasia is strongly associated with a higher age [48][49][50].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our results showed that CRCs with IGF2 LOI mainly occur in the proximal colon; statistically significant relationships were observed between a proximal tumor site and IGF2 LOI in univariate analysis and logistic regression analysis adjusting for age and sex. This finding agrees with the finding of a previous report that CRC with IGF2 LOI is preferentially located in the proximal colon [21]. In the present study, IGF2 LOI seemed to be another factor of carcinogenesis on the right side of the colon independent of aging, whereas our colleagues have reported that right-side colorectal neoplasia is strongly associated with a higher age [48][49][50].…”
Section: Discussionsupporting
confidence: 94%
“…LOI in human tumors leads to a 2-to 3-fold increase in the IGF2 levels in both normal and tumor tissues [17,18]. The IGF2 LOI is highly detected in CRC, adenoma, and normal colorectal mucosa adjacent to colorectal tumors [19][20][21][22]. Furthermore, a mouse model of IGF2 LOI crossed with APC/Min mice developed twice more intestinal tumors than control littermates [23], suggesting that IGF2 LOI in nonneoplastic tissue may be one mechanism by which epigenetic changes affect colorectal tumorigenesis.…”
Section: Introductionmentioning
confidence: 98%
“…From our data, IGF-II imprinting alterations also occurred in adjacent TAN tissue in 4 of 11 (36%) paired UCB cases, with 2 cases showing coordinated IGF-II LOI in both the tumor and TAN, a novel finding for this tumor type but well documented for colorectal cancer where efforts have been taken to decipher the significance of IGF-II LOI in normal tissue (3,27,28). From these studies, it has been shown that IGF-II LOI in normal tissue is associated with a 5-fold increased risk of adenoma formation (3).…”
Section: Discussionmentioning
confidence: 56%
“…In addition, LOI of IGF2 is common (27%) in the general population and those with LOI of IGF2 in normal colonic mucosa have a five-fold increased risk of adenoma formation [30]. Interestingly, poorly differentiated or mucinous carcinomas and proximal lesions were strongly associated with LOI, but there was no statistically significant difference in LOI of IGF2 between tumors with or without MSI [31].…”
Section: Loss Of Imprinting Of Igf-iimentioning
confidence: 98%